Analysis of Curriculum Development Models and Approaches in the Perspective of Modern Education - Muhammad Efendi; Akhmad Syahri; Musta'in (IQRO: Journal of Islamic Education, 2025)
This study aims to analyze curriculum development models and approaches from a modern educational perspective and their contribution to improving the quality of learning. The study used a qualitative approach with library research through the review of various relevant literature sources, such as scientific books, journal articles, and previous research results. Data analysis was conducted descriptively and analytically by reviewing, comparing, and synthesizing various concepts of curriculum development models and approaches. The results show that curriculum development models in modern education, such as rational, interactive, and systemic models, remain relevant but need to be integrated and adapted to dynamic learning needs. Meanwhile, curriculum development approaches that include competency-based, constructivist, experience-based, and integrative approaches emphasize active, contextual, and learner-centered learning. The integration of these models and approaches has been proven to improve the quality of learning, especially in the development of critical, creative, collaborative, and communicative thinking skills. However, the implementation of curriculum development in modern educational practices still faces various challenges, such as limited teacher competency, minimal supporting facilities, and resistance to change. Therefore, strategic efforts are needed to improve educator capacity, strengthen education policies, and optimally utilize learning technology. Thus, curriculum development is expected to produce a learning system that is adaptive, innovative, and relevant to the demands of modern education.